Topological Spaces with Skorokhod Representation Property - Banakh, T.O.; Bogachev, V.I.; Kolesnikov, A.V. (Український математичний журнал, 2005)
We give a survey of recent results that generalize and develop a classical theorem of Skorokhod on representation of weakly convergent sequences of probability measures by almost everywhere convergent sequences of mappings.